The Effect of Profitability and Liquidity on The Company's Value at PT. Indosat Tbk - Septia Isnaeni, Erin; Hernawati, Euis (International Journal of Management and Business, 2025)
This study examines the influence of profitability and liquidity on the valuation of PT. Indosat Tbk. This research employs a quantitative methodology utilizing multiple linear regression analysis methodologies. We assess the company's valuation by comparing its price to book value, evaluate profitability by return on equity, and study liquidity through the current ratio. This study was performed at PT. Indosat Tbk, utilizing annual financial statements available on the IDX for the period from 2020 to 2024. The study's findings indicate that the profitability variable exerts a positive and considerable influence on the company's value, leading investors to prioritize more lucrative long-term factors. Conversely, the liquidity variable does not influence the company's value, signifying that variations in liquidity do not affect it. Profitability and liquidity concurrently exert a substantial impact on the company's value in PT. Organizations should prioritize methods that enhance profitability, including market expansion, product innovation, and cost efficiency, to increase their value.